Association of loneliness and social network size in adulthood with childhood maltreatment: Analyses of a population-based and a clinical sample. Issue 1 (5th September 2022) - Reinhard, Matthias A.; Rek, Stephanie V.; Nenov-Matt, Tabea; Barton, Barbara B.; Dewald-Kaufmann, Julia; Merz, Katharina; Musil, Richard; Jobst, Andrea; Brakemeier, Eva-Lotta; Bertsch, Katja; Padberg, Frank
Abstract: Background: Perceived loneliness and objective social network size are related but distinct factors, which negatively affect mental health and are prevalent in patients who have experienced childhood maltreatment (CM), for example, patients with persistent depressive disorder (PDD) and borderline personality disorder (BPD). This cross-diagnostic study investigated whether loneliness, social network size, or both are associated with self-reported CM. Methods: Loneliness and social network size were assessed in a population-based sample at two time points (Study 1, N  = 509), and a clinical group of patients with PDD or BPD (Study 2, N  = 190) using the UCLA Loneliness Scale and the Social Network Index. Further measures were the Childhood Trauma Questionnaire, and standard depression rating scales. Linear regression analyses were applied to compare associations of loneliness or social network size with CM. Multiple mediation analyses were used to test the relative importance of loneliness and social network size in the relationship between CM and depressive symptoms. Results: In both studies, loneliness showed a stronger association than social network size with CM. This was particularly marked for emotional neglect and emotional abuse. Loneliness but not social network size mediated the relationship between CM and depressive symptoms. Conclusions: Loneliness is particularly associated with self-reported CM, and in this respect distinct from the social network size. Our results underline the importance of differentiating both psychosocial constructs and suggest focusing on perceived loneliness and its etiological underpinnings by mechanism-based psychosocial interventions.